Counseling on the Negative Impacts of Frequent Glue Sniffing Behavior in Children and Adolescents - Safitri, Riri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Repeatedly sniffing glue can cause serious negative impacts, both physically, psychologically, and socially. Medically, chemicals in glue such as toluene or other solvents can damage the central nervous system, cause respiratory disorders, liver and kidney damage, and reduce cognitive function. In the long term, this habit can have an impact on decreased learning ability, emotional disorders, and even a tendency towards criminal acts. Education and socialization about the negative impacts of sniffing glue need to be carried out continuously as a preventive measure. Therefore, the author conducted educational activities in the form of counseling about the negative impacts of frequent glue sniffing behavior on children and adolescents at LKP Universal Technology Computer. This activity is a community service activity that aims to provide children with an understanding of the dangers of using glue as a substance that is abused, as well as to encourage the formation of a healthy and safe environment for children's growth and development. Counseling activities are carried out using the lecture method as the main approach in delivering the material. The percentage value of the questionnaire acquisition of the counseling participants before being given the material exposure is still in the low to moderate range where the most in the low value group with the percentage value of the questionnaire acquisition achieved from the low value group is 85% (17 participants), the moderate value group is 15% (3 participants), while the high value group is 0%. (0 participants). Furthermore, the percentage value of the questionnaire acquisition of the counseling participants after being given the material exposure obtained an increase in knowledge, namely in the moderate to high range, where the most in the high value group, with the low value group being 0% (0 participants), in the moderate value group being 45% (9 participants), then in the high value group being 55% (11 participants). This shows that the counseling activities carried out are able to increase the knowledge of counseling participants about the negative impacts of the behavior of often sniffing glue. Furthermore, it is hoped that with the delivery of this material, counseling participants can avoid and not engage in deviant behavior such as often sniffing glue (ngelem).